Gaelicisation and identity in the 'four obedient shires' of Ireland, 1399-1534 - Booker, Sparky (Trinity College (Dublin, Ireland). Department of History, 2011)
This thesis examines gaelicisation in the ‘four obedient shires’ of the English colony in Ireland from 1399-1543. This region was thought of by contemporaries, and subsequently has been treated by historians, as the most English part of English Ireland. There is some merit in this argument, in that the region was firmly politically English; culturally, however, it was profoundly influenced by its contact and engagement with Irish culture. This thesis argues that the English settlers who lived in this region were far more gaelicised than has been previously acknowledged. This gaelicisation may have been the result of the high Irish population of the region, which included both anglicised Irish people who were of long tenure in the colony, and also a significant number of more recent, and more gaelicised Irish immigrants. The numbers of these Irish migrants, many of whom came from areas of the island that were controlled politically by the Irish, swelled in the fifteenth and sixteenth centuries.
Keywords: History, Ph.D.; Ph.D. Trinity College Dublin